(untitled) (Research, Society and Development, 2020)
Campylobacter jejuni is a bacteria that is involved in the causality of several pathologies, from asymptomatic cases and others with great amplitude to the propensity of death. Its form of acquisition is facilitated, and the human being can become infected by the consumption of contaminated water and food, prepared incorrectly or under poor hygiene techniques. Because it has the possibility of adhesion and synthesis of toxins, there is a large-scale increase in its potential for pathogenicity. In Brazil, this microorganism is detected in cases of gastroenteritis in children. In developed countries it is the main cause of traveler’s diarrhea. This work addresses the morphological characteristics of Campylobacter jejuni, its virulence and epidemiology factor, in addition to the possible diseases caused. To carry out the research, a literature review was carried out, based on publications indexed in the databases: Scielo Google Scholar and Pubmed, published between 2010 and 2020. The descriptors used were: Campylobacter Infections; Gastroenteritis; Campylobacter jejuni, where there were 731 articles, with only 44 selected. The Polymerase Chain Reaction, for measuring the genes of the CDT, is a differential for infectious, always combined with other laboratory and clinical data for a conclusive diagnosis. The use of antimicrobials for the treatment, prevention and / or growth of animals for slaughter has led to an increase in cases of resistance related to microbiota, including C. jejuni.